Arginine Methyltransferases as Regulators of RNA-Binding Protein Activities in Pathogenic Kinetoplastids - Campagnaro, Gustavo D.; Nay, Edward; Plevin, Michael J.; Cruz, Angela K.; Walrad, Pegine B. (Frontiers in Molecular Biosciences, 2021)
A large number of eukaryotic proteins are processed by single or combinatorial post-translational covalent modifications (PTMs) that may alter their activity, interactions and fate. The set of covalent modifications of each protein may be considered a “regulatory code”. Among the PTMs, arginine methylation, catalyzed by protein arginine methyltransferases (PRMTs), can affect how a protein interacts with other macromolecules such as nucleic acids or other proteins. In fact, many RNA-binding proteins (RBPs) are targets of PRMTs. The methylation status of RBPs may affect the expression of their bound RNAs and impact a diverse range of physiological and pathological cellular processes. Unlike most eukaryotes, Kinetoplastids have overwhelmingly intronless genes that are arranged within polycistronic units from which mature mRNAs are generated by trans-splicing. Gene expression in these organisms is thus highly dependent on post-transcriptional control, and therefore on the action of RBPs. These genetic features make trypanosomatids excellent models for the study of post-transcriptional regulation of gene expression. The roles of PRMTs in controlling the activity of RBPs in pathogenic kinetoplastids have now been studied for close to two decades with important advances achieved in recent years. These include the finding that about 10% of the Trypanosoma brucei proteome carries arginine methylation and that arginine methylation controls Leishmania:host interaction. Herein, we review how trypanosomatid PRMTs regulate RBP activity, including modulating RNA interactions and protein complex formation, and discuss how this impacts cellular and biological processes. We further highlight unique structural features of trypanosomatid PRMTs and how it contributes to their singular functionality.